2015
DOI: 10.1007/978-3-319-19800-2_35
|View full text |Cite
|
Sign up to set email alerts
|

Fully Discrete Energy Stable High Order Finite Difference Methods for Hyperbolic Problems in Deforming Domains

Abstract: A time-dependent coordinate transformation of a constant coefficient hyperbolic system of equations is considered. We use the energy method to derive well-posed boundary conditions for the continuous problem. Summation-by-Parts (SBP) operators together with a weak imposition of the boundary and initial conditions using Simultaneously Approximation Terms (SATs) guarantee energy-stability of the fully discrete scheme. We construct a time-dependent SAT formulation that automatically imposes the boundary condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…With the recently derived interface treatment, it can be shown that the scheme is strongly stable and mimics the continuous estimate in (15). This was previously done in [13] and we do not repeat those derivations here.…”
Section: Stabilitymentioning
confidence: 75%
See 4 more Smart Citations
“…With the recently derived interface treatment, it can be shown that the scheme is strongly stable and mimics the continuous estimate in (15). This was previously done in [13] and we do not repeat those derivations here.…”
Section: Stabilitymentioning
confidence: 75%
“…By substituting (14) in (13) and considering the initial conditions U(0, ξ , η) = f L and V (0, ξ , η) = f R , we arrive at to the non-negative and negative eigenvalues, respectively. At the interface, we have n L = (1, 0) T , n R = (−1, 0) T and therefore C L = A L I and C R = −A R I .…”
Section: Well-posednessmentioning
confidence: 99%
See 3 more Smart Citations